Accelerating climate action in unfavourable local contexts: the role of policy entrepreneurship - Alfie Gaffney (npj Climate Action)
Abstract Local authorities are increasingly expected to lead on net-zero delivery, irrespective of their capacity to do so. Existing literature has favoured descriptive accounts of local authorities governing large, well-resourced cities over analysis of those operating in more unfavourable contexts. Consequently, the extent to which most local authorities can act, let alone lead, on climate change, and how policy entrepreneurs can exert agency in such settings, remains understudied. This paper addresses these gaps, examining how Blackpool Council, UK – a least-likely crucial case of climate action in unfavourable contexts – produced a relatively high-quality climate action plan. Analysis of policy documents and elite/expert interviews reveals the crucial role of collective local policy entrepreneurship. The motives and strategies pursued by a group of policy actors significantly accelerated climate action in an innovative, timely, and effective way. Finally, the paper calls for more research into similarly ambitious policy entrepreneurship within other puzzlingly (un)favourable contexts.